'Living' in Nage, or the Meaning of 'Life' in an Eastern Indonesian Society. Issue 2 (6th April 2018) - Forth, Gregory
Abstract : Originating in 19th century cultural evolutionary theory, a revised concept of 'animism' has in recent years found new life in anthropology in the writings of ontological relativists. Continuity is found in the reputed attribution of life by members of small‐scale non‐western societies to inanimate objects as well as to organisms. This new animism is typically contrasted with western or modern scientific thought, either exclusively or primarily. Concerning the Nage of the Indonesian island of Flores, this paper analyzes results of research into what things people regard as being alive ( muzi ). While the majority of Nage deem only animals, plants, and humans to be living, differences appear among informants distinguished by age and gender. As well as the overall finding, this variation and cultural usages contextually depicting certain inanimate objects as being alive raise questions about animism as a unitary way of knowing the world characteristic of single societies.